Explaining National Differences in the Size and Industrial Distribution of Employment - Steven J. Davis; Magnus Henrekson (The Research Institute of Industrial Economics (IUI), 1997)
What factors determine national differences in the size and industry distribution of employment? This study stresses the role of business taxation, employment security laws, credit market policies, wage-setting institutions and the size of the public sector. We characterize these aspects of the economic policy environment in Sweden prior to 1990-91 and compare them to the situation in other European countries and the United States. Our characterization and international comparisons show that Swedish policies strongly disfavored less capital-intensive firms, smaller firms, entry by new firms, and individual and family ownership of business. We also compile evidence that these policies affect outcomes. Taking the U.S. industrial distribution as a benchmark that reflects a comparatively neutral set of policies and institutions, Sweden's employment distribution in the mid-1980s is sharply tilted away from low-wage industries and industries with greater employment shares for smaller firms and establishments. The Swedish rate of self-employment in the 1970s and 1980s is the lowest among all OECD countries. Compared to other European countries, Sweden has an unusually high share of employment in large firms.
Keywords: H30; J21; L52; 330; Business Taxation; Industrial Policy; Industry Structure; Size Distribution; Industriestruktur; Beschäftigungsstruktur; Betriebsgrößenstruktur; Schweden; Europa; USA